2022
DOI: 10.21203/rs.3.rs-2009475/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive knowledge about HIV/AIDS and associated factors among adolescent girls in Rwanda: a nationwide cross-sectional study 

Abstract: Background Limited comprehensive knowledge of HIV/AIDS is highlighted as one of the major factors linked to the high prevalence of HIV among adolescents and young girls. Thus, it is crucial to identify factors that facilitate or hinder adolescent girls from having comprehensive knowledge of HIV/AIDS. We, therefore, assessed the prevalence of comprehensive knowledge about HIV/AIDS and associated factors among adolescent girls in Rwanda. Methods We used secondary data from the Rwanda Demographic and Health Sur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…It was observed that sexually active women belonging to Protestant and "Other" religions (Moslem, Jehovah's witness) had higher odds of indulging in risk factors for HIV infection compared to the Catholics. The ndings are consistent with a study in Rwanda [37] which reported that Catholic respondents were less likely to participate in sexual risk behaviour because they had more comprehensive HIV knowledge due to HIV awareness messages and HIV testing encouraged compared to their protestant counterparts. The nding may be attributed to the different beliefs, values and norms associated with various religions [38,39].…”
Section: Discussionsupporting
confidence: 89%
“…It was observed that sexually active women belonging to Protestant and "Other" religions (Moslem, Jehovah's witness) had higher odds of indulging in risk factors for HIV infection compared to the Catholics. The ndings are consistent with a study in Rwanda [37] which reported that Catholic respondents were less likely to participate in sexual risk behaviour because they had more comprehensive HIV knowledge due to HIV awareness messages and HIV testing encouraged compared to their protestant counterparts. The nding may be attributed to the different beliefs, values and norms associated with various religions [38,39].…”
Section: Discussionsupporting
confidence: 89%
“…The different studies indicated that the mosquito net methods are more frequently used by the most of population of both rural and urban communities in Rwanda because they are available, affordable, and easy to be used effectively. One of the studies conducted in Southern Rwanda showed that although coverage of mosquito bed nets was high (84.1%), their utilization among pregnant women was lower (81.7%) than the national target of 85% (Joseph Kawuki et al, 2023) [9]. Insect repellents are applied on the skin and give short term against mosquito bites.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, Human Immunodeficiency Virus and Acquired Immune Deficiency Syndrome (HIV/AIDS) remains a public health concern and Sub-Saharan Africa (SSA) has the greatest burden (Organisation, 2022). Over 38 million people are infected with HIV worldwide, with women making up more than half (19.2 million) of the infected (Kawuki, J et al.2023). Sub-Saharan African women account for 15.9 million of the 19.2 million total (UNAIDS., 2020).…”
Section: Introductionmentioning
confidence: 99%